Information and communication for natural resource management in agriculture : (Food and Agriculture Organization of the United Nations, 2006)
Information and communication for NRM: An overview, participatory communication and learning for natural resource management in agriculture (NRMA), participatory rural communication appraisal (PRCA), planning strategic communication in NRMA, participatory message and materials development, management and implementation of communication programs in NRMA, monitoring and evaluation of communication, lesson in capacity building in ICNRMA in Cambodia.